Electrochemical Detection of Neuraminidase Based on Zanamivir Inhibition Reaction at Platinum and Platinum-Modified Boron-Doped Diamond Electrodes - Ivandini, Tribidasari Anggraningrum; Ariani, Jenny; Jiwanti, Prastika Krisma; Gunlazuardi, Jarnuzi; Saepudin, Endang; Einaga, Yasuaki (UI Scholars Hub, 2017)
Neuraminidase sensors have been developed using platinum (Pt) and platinum-modified boron-doped diamond (Pt-BDD) electrodes based on the difference of electrochemical responses of zanamivir in the absence and in presence of neuraminidase. Cyclic voltammetry of zanamivir showed that the presence of zanamivir decreases the oxidation-reduction peak currents of Pt. The responses were found to be linear in the zanamivir concentration range of 7.5-150 μM. Comparison between Pt-BDD and Pt bulk electrodes showed that Pt-BDD offers approximately two times higher sensitivity of zanamivir responses than Pt bulk. Further comparison to gold-based electrodes showed that Pt-based electrodes provided about one order higher sensitivity of zanamivir responses. In the presence of neuraminidase, the oxidation-reduction currents of Pt again increase. Observation on the oxidation currents in the system with 2 x 10-5 M zanamivir showed that the responses were linear in the neuraminidase concentration range of 5-20 mU. Good reproducibility with an RSD < 3 (n = 10) was achieved even when the measurements were performed in a mucin matrix,suggesting that Pt-based electrodes are suitable to be applied for the detection method of neuraminidase.